The Performance of REDD+: From Global Governance to Local Practices - Arts, Bas; Ingram, Verina; Brockhaus, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
REDD+ represents countries' efforts to reduce emissions from deforestation and forest degradation, and foster conservation, the sustainable management of forests, and the enhancement of forest carbon stocks. The basic idea is that more carbon can be sequestrated and stocked in tropical forests by improving their conservation, management, and sustainable use, thus contributing to mitigating climate change. The developing countries and relevant stakeholders concerned will be financially compensated for these endeavors, either through public funds or private carbon markets. Given this context, this book will address the need to assess the political and socio-economic dimensions of the performance of REDD+, which is relevant to policy-makers, practitioners, and scholars. This implies taking into account the various levels (from global to local) and dimensions (e.g., results-based payments, MRV, co-benefits, and community engagement), as well as divergent (disciplinary) connotations, of performance. We, therefore, pose the following question: What does performance mean? In answering this question, we provide examples of assessments of performance. We present 9 cases of how REDD has performed on local, national and international scales, and reflect on the representativeness of these examples and their limitations when looking at the current range of REDD initiatives, along with what is missing in terms of evaluating the performance of REDD+. We conclude by establishing why performance assessment remains so relevant today.